2002
DOI: 10.1007/s100670200104
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Inflammatory Myopathy with Diffuse Alveolar Damage

Abstract: Interstitial lung disease (ILD) in patients with myositis is defined by the presence of interstitial changes on radiographic examination. The reported prevalence of ILD varies from 0% to nearly 50%. However, only rarely has the pathological pattern of diffuse alveolar damage (DAD) associated with idiopathic inflammatory myopathy (IIM) been reported. We report five patients with IIM (one with dermatomyositis, one with polymyositis, and three with amyopathic dermatomyositis) and respiratory failure. Four underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
60
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 14 publications
0
60
0
1
Order By: Relevance
“…As ADM is a rare disease, previous studies of ILD-ADM included only one, or a few patients [7][8][9][10][11][12][13]. The present study investigated the highest number of patients with ILD-ADM so far.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…As ADM is a rare disease, previous studies of ILD-ADM included only one, or a few patients [7][8][9][10][11][12][13]. The present study investigated the highest number of patients with ILD-ADM so far.…”
Section: Discussionmentioning
confidence: 98%
“…To date, contradictory data have been reported in the prognosis of ILD-ADM. Previous studies, mainly from Asia, have demonstrated that ILD-ADM generally runs an aggressive course, leading to fatal respiratory failure [7][8][9][10][11][12]. In contrast, COTTIN et al [13] recently described a benign form of ILD-ADM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Tazelaar [18], polymyositis or dermatomyositis may be accompanied by either usual interstitial pneumonia (UIP), diVuse alveolar damage (DAD) or bronchiolitis obliterans organizing pneumonia (BOOP, now called COP). DiVuse alveolar damage is reported to have the worst prognosis and bronchiolitis obliterans organizing pneumonia (BOOP/COP) has the most favorable prognosis [10,15,19]. Anti-SRP antibodies, which are mainly polymyositis speciWc, may also be found in dermatomyositis or systemic sclerosis [5,9,13].…”
Section: Discussionmentioning
confidence: 99%